An Exploratory Analysis of the Role of Adipose Characteristics in Fulltime Wheelchair Users’ Pressure Injury History - Sonenblum, Sharon Eve; Measel, Megan; Sprigle, Stephen H.; Greenhalgh, John; Cathcart, John McKay (Frontiers in Bioengineering and Biotechnology, 2021)
Aim: The goals of this study were 1) to identify the relationship between adipose (subcutaneous and intramuscular) characteristics and pressure injury (PrI) history in wheelchair users and 2) to identify subject characteristics, including biomechanical risk, that are related to adipose characteristics. Materials and Methods: The buttocks of 43 full-time wheelchair users with and without a history of pelvic PrIs were scanned in a seated posture in a FONAR UPRIGHT® MRI. Intramuscular adipose (the relative difference in intensity between adipose and gluteus maximus) and the subcutaneous adipose characteristics (the relative difference in intensity between subcutaneous adipose under and surrounding the ischium) were compared to PrI history and subject characteristics. Results: Participants with a history of PrIs had different subcutaneous fat (subQF) characteristics than participants without a history of PrIs. Specifically, they had significantly darker adipose under the ischium than surrounding the ischium (subQF effect size = 0.21) than participants without a history of PrIs (subQF effect size = 0.58). On the other hand, only when individuals with complete fat infiltration (n = 7) were excluded did individuals with PrI history have more fat infiltration than those without a PrI history. The presence of spasms (μ intramuscular adipose, 95% CI with spasms 0.642 [0.430, 0.855], without spasms 0.168 [−0.116, 0.452], p = 0.01) and fewer years using a wheelchair were associated with leaner muscle (Pearson Corr = −0.442, p = 0.003). Conclusion: The results of the study suggest the hypothesis that changes in adipose tissue under the ischial tuberosity (presenting as darker SubQF) are associated with increased biomechanical risk for pressure injury. Further investigation of this hypothesis, and the role of intramuscular fat infiltration in PrI development, may help our understanding of PrI etiology. It may also lead to clinically useful diagnostic techniques that can identify changes in adipose and biomechanical risk to inform early preventative interventions.